MODEL BANGKITAN PERGERAKAN PEKERJA BERDASARKAN TINGKAT PENDAPATAN RUMAH TANGGA (STUDI KASUS KOTA BANDA ACEH) - Putri Balqis; Renni Anggraini; Sugiarto Sugiarto (Prodi Magister Teknik Sipil Unsyiah, 2018)
In general, within a household, almost every day do several Activities or movements. Going to work is an activity that most frequently performed within households. The activity can support or meet the needs of the household life. In this study, worker trip generation is modeled based on the aggregation of household's income level. Firstly, household income is divided into two categories namely low income (≤ IDR 5 million) and high income (greater than IDR 5 million). This study aims to formulate the differences in utility faction, the trip probability, and factors that influencing work trip activities. The data were collected within four sub-districts located in Banda Aceh province such as Jaya Baru, Banda Raya, Lueng Bata and Kuta Raja. About 400 questionnaire survey is collected and used for this study. The binomial logit model is applied to model worker trip activities, and parameters estimation is determined using SPSS. The empirical result from the analysis shows us that for a model of worker trip generation by low income is obtained the utility difference value is 0,314, probability value 55% and 45% for trip lower than 4 and ≥ 4, respectively. The factors that are influence the model is the number of car ownership, family members, family members who have not attended school and destination location.Furthermore, the model of worker trip generation based for high-income household was obtained utility difference value is 0,867, a probability value is 67% and 33% for trip lower than 4 and ≥ 4, respectively. The factors that influenced the model are the number of motorcycle ownership, family members who attended school, family members who have not attended school, family members who work, the age of respondent, and activity duration.